Comparing Concrete and Virtual Manipulatives to Teach Algebra to Middle School Students with Disabilities. Issue 1 (1st January 2023) - Bone, Erin K.; Bouck, Emily C.; Satsangi, Rajiv
ABSTRACT: Manipulatives are an effective mathematical tool to support students with disabilities in the area of mathematics. Yet, there remain inconsistencies in terms of which type – concrete or virtual – is more effective for students with disabilities working on algebra related content and which type is preferred by students. The researchers used an alternating treatment single case research design to compare the effectiveness of each type of manipulative in terms of students' accuracy and independence when using the tools. Results indicate both types of manipulatives were effective in terms of accuracy no notable differences when comparing independence. However, when reviewing social validity interview data, all three students preferred virtual algebra tiles.